Elevated Plasma Homocysteine Levels in Anti-N-methyl-D-aspartate Receptor Encephalitis - Liu, Lizhi; Liang, Jie; Liu, Qing; Luo, Chongliang; Liu, Jia; Fan, Rong; Chen, Zhigang; Chen, Yong; Peng, Fuhua; Jiang, Ying (Frontiers in Neurology, 2019)
Objective: Homocysteine (Hcy) levels have been investigated in many diseases, such as neurodegenerative and autoimmune diseases. However, changes in Hcy levels in anti-N-Methyl-D-aspartate receptor (anti-NMDAR) encephalitis have not been investigated thus far. Methods: Case data were collected from 46 patients with anti-NMDAR encephalitis and 179 age- and sex-matched healthy controls (HCs). Clinical characteristics, Hcy levels, C reactive protein (CRP) levels, and cerebrospinal fluid (CSF) parameters were determined. Association of Hcy and clinical parameters were evaluated in these patients. Among these 46 patients, 15 had a follow-up evaluation at 3 months after treatment. Results: Hcy levels (p<0.001) and CRP levels (p =0.003) from the patients with anti-NMDAR encephalitis were significantly higher than those from HCs. Hcy levels from male patients were significantly lower than those from male HCs (p < 0.001). Comparing anti-NMDAR encephalitis patients after treatment with before treatment, the former has significantly lower Hcy levels (p = 0.004), CRP levels (p = 0.041) and mRS scores (p = 0.002). Furthermore, a significant negative correlation between the changes in Hcy levels and the changes in mRS scores (r = -0.534, p=0 .040) was observed. Conclusion: Elevated Hcy level may play a role in the pathogenesis or progression of anti-NMDAR encephalitis.